Perception of climate change and driving factors for the adoption of drought tolerant rice varieties in Bangladesh - MD REZAUL KARIM; MD. ABDUL MAJID PRAMANIK; NOOR MUHAMMAD; ATAHARUL CHOWDHURY; MD. KHALID AURANGOZEB; REBEKA SULTANA (Asian Journal of Agriculture, 2026)
Abstract. Karim MR, Pramanik MAM, Muhammad N, Chowdhury A, Aurangozeb MK, Sultana R. 2026. Perception of climate change and driving factors for the adoption of drought tolerant rice varieties in Bangladesh. Asian J Agric 10 (1): g100137. https://doi.org/10.13057/asianjagric/g100137. The adoption of Drought Tolerant Varieties (DTV) of rice can be a significant solution to combat water scarcity and reduce grain yield loss. The main objective of the study is to determine farmers’ perceptions of climate change and to explore the drivers of the adoption of drought tolerant rice varieties. The study was conducted in two villages of Farakkhabad Union Parishad of Biral Upzila under Dinajpur District of Northern Bangladesh. The data were collected from 181 sampled rice farmers who experienced seasonal drought in crop cultivation due to decreasing rainfall over the years. The observed meteorological data on temperature and rainfall closely aligned with perceptions of climate change. The study found that 61.32% of farmers adopted the drought tolerant rice varieties. The logit regression analysis showed that eight factors, such as gender, education, farm size, income, training access, extension service, credit access, and access to Information, Communication and Technology (ICT), significantly influenced the adoption of drought tolerant rice varieties. Non-adopter farmers cited a lack of information, unavailability of seeds, and a lack of cash to purchase seeds as major obstacles to the adoption of drought tolerant rice varieties. Therefore, in term of novelty, this study highlights and incorporates the institutional factors along with socio-economic factors of the rice farmers by indicating their climate change perception and aligning with meteorological data. The study recommends that different government and non-government extension programs can promote institutional services for training, credit and information acccess to overcome the challenges of non-adoption. Further relevance policies and uptake programs could accelerate the adoption of drought tolerant rice varieties to cope with the impacts of drought.